Nickel exposure induced endoplasmic reticulum stress by disturbing calcium homeostasis and triggered mitochondrial autophagy in domestic animal oocytes - Chengkun Zhong; Shengkui Hou; Jing Guo; Jing Zhao; Jun Wang; Yi Fang; Hongyu Liu; He Ding; Xin Ma; Wenfa Lyu (Ecotoxicology and Environmental Safety, 2025)
Nickel, a heavy metal with industrial applications and as a feed additive for livestock, can adversely impact reproductive function and gamete quality when present in excessive amounts in the animal feed environment. In this study, the results indicate that nickel exposure hampers polar body extrusion and cumulus cell expansion, thereby diminishing oocyte quality and developmental competence. Furthermore, nickel exposure reduces glutathione (GSH) levels in oocytes, leading to excessive accumulation of reactive oxygen species (ROS), provoking oxidative stress and mitochondrial impairment. This cascade initiates mitochondrial autophagy, upregulates the expression of autophagy-related proteins Parkin and PINK1, promotes LC3 binding to autophagosomes. Nickel exposure disrupts calcium homeostasis and induces endoplasmic reticulum stress (ERS). Inhibiting ERS effectively alleviates the deterioration of oocytes quality caused by nickel exposure and inhibits mitochondrial autophagy. Proteomics further confirms nickel’s exposure detrimental effects on mitochondria and ER, impacting cellular processes. Employing bovine oocytes as a model, consistent phenotypes were observed. These results indicate that nickel exposure disrupts intracellular calcium homeostasis, elicits ERS, disrupts cellular calcium homeostasis, diminishes the quality of pig oocytes, impairs oocyte maturation and developmental potential, and instigates mitochondrial autophagy.